Peran Bank Sentral dalam Menangani Maraknya Peredaran Uang Palsu di Hari Raya Idul Fitri - Dia Agustia Salsabila; Septiana Sihombing; Imel Aulia; Reski Mauliana; Sisil Pratisia (Jurnal Multidisiplin Ibrahimy, 2025)
As the Eid Al-Fitr Holiday approaches, the public’s demand for cash increases significantly, especially for Holiday Allowance. This situation is often exploited by irresponsible individuals to circulate counterfeit money. This article discusses the strategic role of the central bank in combating the increased circulation of counterfeit money that occurs each Eid. Through qualitative methods and a descriptive approach, this research examines secondary data from various sources, including official reports from the central bank. The study results show that the central bank actively maintains economic stability through currency verification services, providing expert testimony in legal processes, strengthening the security features of new currency, and educating the public through the Love, Proud, Understanding Rupiah program. The decrease in the ratio of counterfeit money from year to year reflects the success of the preventive and educational measures taken by the central bank.